ANTARA TO MINAA, ADAT-KEBUDAYAAN TORAJA, DAN KEKRISTENAN - Christian Briand Samulung; Windy Pricilia Pangadongan, Lilis Vira Pala'langan, Nelsa Rosalina, Lusiani Buan (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This paper aims to explore the function of To Minaa in Torajan culture. Through this study, the research continues to try to understand how elements of Christianity can interact with and influence the implementation of the function of To Minaa in the context of Torajan traditional rituals. In this study, there are informants who provide data related to the study, who are considered to have knowledge about the function of To Minaa. The method used in this research is descriptive qualitative by providing an explanation of the meaning and function of To Minaa. Then, the data analysis technique used in this study is qualitative data analysis, with the aim of revealing pre-existing data found in the field, so that the explanation of the problem discussed can find a bright spot. Afterwards, there will be an assessment based on the Biblical elements in the Christian perspective using the translation model approach. Where the function of this translation model is as a benchmark for the context that occurs, so that it can be in line with Christian values. From the results of the research conducted, it was found that the function of To Minaa in the traditional rituals of the Toraja people is emphasized on the words spoken or "kada-kada To Minaa" which are actually full of meaning. So it cannot be concluded as a complement in traditional rituals alone. So it cannot be concluded that it is merely a complement to the traditional ritual. Therefore, it is hoped that Christianity can take part in this traditional ritual, including the purpose of expressing the kada-kada To Minaa which should contain elements of Christian theology